2017
DOI: 10.1172/jci90592
|View full text |Cite
|
Sign up to set email alerts
|

Altered homeostatic regulation of innate and adaptive immunity in lower gastrointestinal tract GVHD pathogenesis

Abstract: Acute graft-versus-host disease (aGVHD) was noted as a complication of allogeneic bone marrow (BM) transplantation in animal models more than six decades ago (1, 2). The initial descriptions of aGVHD differentiated it from the complications of BM aplasia and focused on the severe consequences of GVHD for lower gastrointestinal (GI) tract function, as manifested by weight loss and profound diarrhea. Subsequent studies clearly identified donor T cells as the critical cells required for the induction of aGVHD (3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 173 publications
0
28
0
Order By: Relevance
“…Allogeneic hematopoietic stem cell transplantation (HSCT) is used in the treatment of neoplastic and immune disorders. Graftversus-host disease (GVHD), in which donor-derived T cells target recipient alloantigens to cause tissue pathology, is a common, and frequently severe, complication of HSCT (1). Tissue damage that occurs as a result of pretransplant conditioning is an important factor in GVHD initiation (2,3), and we have demonstrated that this primarily reflects a requirement for intestinal injury and associated barrier loss (4).…”
Section: Introductionmentioning
confidence: 83%
“…Allogeneic hematopoietic stem cell transplantation (HSCT) is used in the treatment of neoplastic and immune disorders. Graftversus-host disease (GVHD), in which donor-derived T cells target recipient alloantigens to cause tissue pathology, is a common, and frequently severe, complication of HSCT (1). Tissue damage that occurs as a result of pretransplant conditioning is an important factor in GVHD initiation (2,3), and we have demonstrated that this primarily reflects a requirement for intestinal injury and associated barrier loss (4).…”
Section: Introductionmentioning
confidence: 83%
“…At the time of this report, 20 of 37 patients are alive and 19 are in complete remission. Six patients received donor lymphocyte infusions owing to disease relapse (5) or incomplete donor engraftment (1). Two of these patients are alive.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Graft-versus-host disease (GVHD) remains a significant barrier to successful allogeneic hematopoietic cell transplantation (allo-HCT) and is the most common cause of treatment-related mortality in patients with hematologic malignancies, especially when the gastrointestinal (GI) tract is involved [1]. Acute GVHD complicates approximately 30% to 50% of HLA-matched transplantations from related donors and 50% to 70% of transplantations from unrelated donors with standard prophylaxis regimens [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although antibiotic treatment in stem cell transplant patients is meant to avoid bacterial infections and is essential in many patients, recent studies link these to a higher risk of developing bacterial infections from opportune pathogens and subsequently graft-versus-host disease (GvHD). A significant number of patients receiving allogenic stem cell transplantation develop GvHD, which causes up to 30% mortality in these patients [9]. …”
Section: Interaction Between the Gut Microbiota And The Host Immune Smentioning
confidence: 99%